Kajian Pembuktian Teori Faktor Utama Transportasi terhadap Nilai Lahan, Kota Soreang - Rifani Ridadikri; Ina Helena Agustina; Riswandha Risang Aji (Bandung Conference Series: Urban & Regional Planning, 2026)
Abstract. This study examines the development of residential land values ​​resulting from the operation of the Soroja Toll Road. The ease of access created through the construction of the toll road has the potential to spur the development of residential land values. The land value is viewed from the perspective of housing, because the housing sector can relatively emerge triggered by the development of the transportation sector. The purpose of this study is to prove Chan's Theory Regarding the Main Factors of Transportation on Land Values ​​with a case study on the Soroja Toll Road in the Soreang City Area. The analysis method used is descriptive statistics. The results of this study found that changes in residential land use occurred increasingly in 2025, before the operation of the Soroja Toll Road, the land value was at IDR 2,000,000 to IDR 3,000,000 / square meter, while after the Soroja Toll Road operated, the land value increased to IDR 4,500,000 to IDR 7,000,000 / square meter, this proves the transportation theory that Toll Roads influence changes in residential land values Abstrak. Studi ini mengkaji perkembangan nilai lahan perumahan yang diakibatkan oleh beroperasinya Jalan Tol Soroja. Kemudahan akses yang tercipta melalui pembangunan jalan tol berpotensi memacu perkembangan nilai lahan perumahan. Nilai lahan tersebut ditinjau dari perumahan, karena sektor perumahan relatif dapat muncul dipicu dari adanya perkembangan sektor transportasi. Tujuan Penelitian ini adalah untuk membuktikan Teori Chan Mengenai Faktor Utama Transportasi Terhadap Nilai Lahan dengan studi kasus di Jalan Tol Soroja Wilayah Kota Soreang. Metode analisis yang digunakan adalah deskriptif statistik. Hasil dari penelitian ini ditemukan perubahan penggunaan lahan perumahan terjadi semakin berkembang di tahun 2025, sebelum beroperasinya Jalan Tol Soroja nilai lahan berada di Rp2.000.000 hingga Rp3.000.000/meter persegi, sedangkan setelah Jalan Tol Soroja beroperasi nilai lahan meningkat menjadi Rp4.500.000 hingga Rp7.000.000/ meter persegi, hal tersebut membuktikan teori transportasi yaitu Jalan Tol berpengaruh terhadap perubahan nilai lahan perumahan.